Biology and management of the banana weevil (Cosmopolites sordidus germar) in the socioeconomic and agroecological context of the indigenous territories of Talamanca, Costa Rica - Dahlquist, Ruth (2008)
Tesis (Ph. D.). -- CATIE, Turrialba (Costa Rica) -- University of Idaho, Idaho (Estados Unidos de América), 2008